Reproductive Health of Women After Pregnancy: Evaluation and Recovery from Physiological and Psychological Impacts - Yenni Kristiana; Ratna Sari Dewi; Dessy Abdullah; Zaenal; Azizah Rahmawati (Oshada, 2025)
Post-pregnancy, women experience complex physiological changes, including decreased hormone levels, trauma to the pelvic muscles, and the risk of complications such as pelvic organ prolapse, urinary incontinence or sexual dysfunction. The process of uterine involution requires attention to prevent complications such as bleeding or infection. A comprehensive medical evaluation including examination of the reproductive organs and nutritional status of the mother is essential to ensure optimal recovery. On the other hand, psychological disorders such as postpartum depression (PPD) and anxiety are common in new mothers, affecting both maternal well-being and infant development. Hormonal fluctuations, social pressures and new responsibilities exacerbate these conditions. Lack of social support and cultural stigma compound the challenges mothers face. Psychotherapy-based interventions and integration of mental health services have proven effective in helping mothers overcome these psychological issues. Structural barriers, such as lack of access to health facilities and limited medical personnel, are obstacles to providing adequate post-pregnancy care. Community-based education programs and strengthened health services are needed to increase awareness and access. With a holistic approach that includes both physical and mental aspects, post-pregnancy recovery can be optimized, improving the overall quality of life for mothers and families.